Pengaruh Partisipasi Penyusunan Anggaran pada Akuntabilitas Kinerja: Budaya Organisasi, Kepuasan Kerja Komitmen dan Organisasi - Gede Pradana, I Gusti Agung; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2018)
This study aims to determine and test empirically the effect of budgeting participation on the performance accountability of government agencies with organizational culture, job satisfaction and organizational commitment as moderating variables. Data collection is done using a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of research conducted show that budget preparation participation has a positive effect on the performance accountability of government agencies. Organizational culture is not able to moderate the influence of budgeting participation variables on the performance accountability of government agencies. Job satisfaction is not able to moderate the influence of budgeting participation variables on the performance accountability of government agencies. Organizational commitment strengthens the influence of budgeting participation on the performance accountability of government agencies. Keywords: Budgeting Participation, Performance Accountability, Organizational Culture, Job Satisfaction, Organizational Commitment